An in vivo evaluation of the safety and efficacy of using decellularized bovine parietal peritoneum membranes as dural substitutes - Doskaliyev, Aidos; Ogay, Vyacheslav; Mussabekov, Islambek; Satov, Muratbek; Zhetpisbayev, Berik; Mustafin, Khalit; Bobrova, Xeniya; Auezova, Raushan; Akshulakov, Serik (Frontiers in Surgery, 2024)
PurposeThe reconstruction of dura matter is a challenging problem for neurosurgeons. A number of materials for dural reconstruction have recently been developed, but some of them have poor biocompatibility, poor mechanical properties, and adverse effects. Bovine parietal peritoneum is a promising natural material for regenerative medicine and reconstructive surgery. In this study, we conducted an in vivo evaluation of the safety and efficacy of using decellularized bovine peritoneum membranes (BPMs) as natural dural substitutes in a rabbit model.MethodsThe dural defects in mature New Zealand rabbits were studied. A BPM was sutured on the dural defect area of each animal. Autologous periosteum and collagen membranes (Lyoplant®) were used to facilitate a comparison with the BPMs. ELISA, histomorphological analysis, and hematological analysis were carried out to examine the safety and efficacy of using BPMs as dural substitutes.ResultsOur results showed that the BPMs demonstrated a deterioration rate that is suitable for gathering newly formed meningothelial tissue. The thickness and density of BPM fibers prevents resorption in the first few days after use as a plastic material, and the regeneration of the dura mater does not occur at an accelerated pace, meaning that the gradual formation of fibrous tissue prevents adhesion to the brain surface. It was observed that the BPM can integrate with the adjacent tissue to repair dural defects. Moreover, the transplantation of BPMs did not cause significant adverse effects or immunological responses, indicating the safety and good biocompatibility of the BPM.ConclusionThus, our in vivo study in a rabbit model showed that decellularized BPMs may represent a biocompatible natural material that can be used in cases requiring dura matter repair without significant adverse effects.